THE RELATIONSHIP BETWEEN SELF-CONCEPT WITH ASSERTIVENESS IN CLASS X STUDENTS KESATRIAN 2 SENIOR HIGH SCHOOL SEMARANG - Anindyta Pusparani; Achmad Mujab Masykur (Faculty of Psychology, Diponegoro University, 2014)
Assertiveness is important for teenagers, that allows teens to put themselves and perform the strategic, directed, controlled and steady activities, so teens can avoid the negative behavior. Assertiveness is consist of by several factors, one of which is influenced by self-esteem. A person with a positive self-esteem has a positive self-concept. This study aims to empirically examine the relationship of self-concept with assertiveness in class X Kesatrian 2 Semarang High School. The samples in this study using cluster random sampling technique and obtained a sample of 104 students. Data mining method using two scales of psychology. 36-item scale with a valid Assertiveness Scale (α = 0.922) and the Self-Concept Scale 36-item valid (α = 0.932). Data were analyzed using simple linear regression. The results showed a correlation coefficient (rxy) of 0.706 with p = 0.000 (p